2013
DOI: 10.1007/s00268-013-2125-3
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Robotic Bariatric Surgery

Abstract: Digital platforms are showing great promise as enabling technology which advance bariatric outcomes. With increasingly complex bariatric cases being performed and revised, the insertion of digital information between the surgeon and the patient leads to better operations for the patient and the surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Consequently, postoperative morbidity rate has been reported from 11 to 38 % when RYGBP is performed after vertical banded gastroplasty (VBG) and from 6 to 46 % after adjustable gastric banding (AGB) [32][33][34][35][36][37][38][39][40][41]. In this setting, the robotic approach has been proposed to perform RYGBP after failed previous bariatric surgical procedures because it is considered to be associated with improved postoperative morbidity in comparison with conventional laparoscopic or open approaches [2,22,29,31,40,42]. Hence, Buchs et al reported that robotic group patients had no postoperative complications whereas postoperative morbidity rates were 14.3 and 10.7 % after conventional laparoscopic and open revisional RYGBP, respectively [42].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Consequently, postoperative morbidity rate has been reported from 11 to 38 % when RYGBP is performed after vertical banded gastroplasty (VBG) and from 6 to 46 % after adjustable gastric banding (AGB) [32][33][34][35][36][37][38][39][40][41]. In this setting, the robotic approach has been proposed to perform RYGBP after failed previous bariatric surgical procedures because it is considered to be associated with improved postoperative morbidity in comparison with conventional laparoscopic or open approaches [2,22,29,31,40,42]. Hence, Buchs et al reported that robotic group patients had no postoperative complications whereas postoperative morbidity rates were 14.3 and 10.7 % after conventional laparoscopic and open revisional RYGBP, respectively [42].…”
Section: Discussionmentioning
confidence: 97%
“…As a majority of new available technologies, R-RYGBP has been adopted in some centers on the basis of large single-and multi-institutional retrospective experiences [3]. We believe this data may not be sufficient to justify the higher cost due to the routine use of a robotic system to perform a gastric bypass in a morbidly obese patient [2,3,8,12]. Furthermore, it is now unjustifiable that new technologies are adopted without a robust system of post marketing surveillance and professional oversight to evaluate safety, efficacy, and cost [1].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Since its military applicability did not develop as initially expected, robotic surgery technology was modified towards the development of equipment which could align the excellent quality of high definition 3-D image, the intuitive movements of the open surgery and the precision, refinement and minimally invasive aspects of laparoscopic surgery. This combination seems to be very useful and beneficial in advanced and complex gastrointestinal surgeries, such as bariatric surgery 14,29 . The first reports on the use of robotic technology in surgery encompassed the hybrid technique ("robot-assisted") where the robot was used in only part in the conventional laparoscopy, mainly in the anastomoses.…”
Section: Discussionmentioning
confidence: 99%